Progresivisme dan Perspektifnya terhadap Pembelajaran di Era Pandemi Covid-19 - Rino Richardo; Hasna Ulayya Eliana; Rima Aksen Cahdriyana (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2021)
This research aims to find and describe the philosophy concept of progressivism and the persepctive toward the learning process in the era of Covid-19 pandemic, as well as the perspective toward learning, educators and students. This research is a library research using books and electronic scientific articles as data sources. In collecting the data, researchers browse online data through the Google scholar database. While the data analysis applied in this study is the content analysis method. The research results show that progressivism as an educational philosophy plays an important role in providing a basis for developing a flexible learning system adapting to the progress and development of science and technology, especially during the Covid-19 pandemic.